Penal Policy: Decriminalization of Election Crimes in Indonesia - Muhammad Azil Maskur; Pujiyono; Irma Cahyaningtyas; Fikri, Wildan Azkal; Zadataqi, Faikar Sir (Pandecta Research Law Journal, 2024)
Several election crime articles in Law No. 7/2017 are suspected of causing injustice to subjects who commit election infractions, particularly civil servants, village heads, and election organizers. The potential for injustice arises because the imposition of election crimes on civil servants, village heads, and election organizers causes all three to receive double jeopardy, although double jeopardy is contrary to the constitution and human rights, meaning that enacting election crimes is unfair to all three. These intrigues should be resolved immediately to achieve legal justice for all three. To answer these dynamics, further research needs to be carried out to find out where the injustice lies and the appropriate solution to overcome it. This research utilizes normative legal or doctrinal to examine injustice and find appropriate advisers. The penal policy approach is the right measure to eliminate injustice in election crime articles in Law No. 7/2017. This injustice is precisely in Articles 490, 494, and 546 of Law No. 7/2017 which regulates criminal sanctions for civil servants, village heads, and election organizers who commit election crimes. Decriminalization of Articles 490, 494, and 546 of Law No. 7/2017 needs to be applied because the application of these three articles has caused civil servants, villages, and election organizers to receive double jeopardy, while double jeopardy is contrary to the constitution and human rights so that the application of these three articles is real injustice.